Answer:
For (x, y) → (3x, 3y)
The coordinates are:
A'(-3, 3), B'(0, 15), C'(3, 6), D'(3, -3)
For (x, y) → (y, x)
The coordinates are:
A'(1, -1), B'(5, 0), C'(2, 1), D'(-1, 1)
For (x, y) → (-x, -y)
The coordinates are:
A'(1, -1), B'(0, -5), C'(-1, -2), D'(-1, 1)
Step-by-step explanation:
For (x, y) → (3x, 3y)
The coordinates are:
A'(-3, 3), B'(0, 15), C'(3, 6), D'(3, -3)
We replaced x by 3x and y by 3y
For (x, y) → (y, x)
The coordinates are:
A'(1, -1), B'(5, 0), C'(2, 1), D'(-1, 1)
We replaced x by y, and y by x
For (x, y) → (-x, -y)
The coordinates are:
A'(1, -1), B'(0, -5), C'(-1, -2), D'(-1, 1)
We replaced x by -x, and y by -y.